IMPLEMENTATION OF VIBE CODING IN THE DEVELOPMENT OF AN INTERNAL QUALITY ASSURANCE MANAGEMENT SYSTEM FOR INTERNAL QUALITY AUDIT (AMI) AND PPEPP BASED ON LAM INFOKOM STANDARDS - Ahmad Syaifuddin; Ronny Makhfuddin Akbar; Hafizh Fianto Putra; Yanuarini Nur Sukmaningtiyas; Anita (IJCDE (Indonesian Journal of Community Diversity and Engagement), 2026)
The Internal Quality Assurance System (IQAS), implemented through the Establishment, Implementation, Evaluation, Control, and Improvement (PPEPP) cycle, is a mandatory requirement for study programs seeking accreditation from the Independent Accreditation Agency for Informatics and Computer Science (LAM INFOKOM). Conventional management of Internal Quality Audit (AMI) documents and Self-Evaluation Reports (LED) often hinders accreditation preparation due to fragmented, inconsistently archived documentation. This community service activity assisted the Quality Assurance Unit at Universitas Islam Majapahit (UNIM) in developing an integrated quality management information system using Native PHP and Tailwind CSS through a vibe coding approach, in which developers with existing web development competence directed an AI programming assistant to generate source code and interface components. The system was completed as a functional prototype within one month, faster than typical conventional development. Following Focus Group Discussion sessions and hands-on mentoring, self-assessed readiness among five participating Quality Assurance Unit members improved across all evaluated aspects. These findings suggest that AI-assisted development, guided by developers with relevant technical competence, offers a practical and time-efficient pathway for institutions with limited programming resources to build internal quality assurance systems aligned with LAM INFOKOM standards.